2007
DOI: 10.1002/ajp.20429
|View full text |Cite
|
Sign up to set email alerts
|

Response to novel food and the role of social influences in common marmosets (Callithrix jacchus) and Goeldi's monkeys (Callimico goeldii)

Abstract: Neophobia, defined as showing caution toward novel features of the environment, is widespread in birds and mammals; it can be affected by ecology, early experience, and social context. In this study, we aimed to (i) investigate the response to novel food in adult common marmosets and Goeldi's monkeys and (ii) assess the role of social influences. We used an experimental paradigm employed previously with capuchin monkeys and children, in which a subject (observer) was presented with a novel food under three con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 55 publications
3
13
1
2
Order By: Relevance
“…In fact, several studies demonstrated that eating is socially facilitated by seeing/hearing others eating food [Ferrari et al, ] and that social facilitation of eating allows tufted capuchin monkeys ( Sapajus spp.) [Addessi et al, ; Visalberghi and Addessi, , ] and human children [Galloway et al, ] to overcome caution toward novel food.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies demonstrated that eating is socially facilitated by seeing/hearing others eating food [Ferrari et al, ] and that social facilitation of eating allows tufted capuchin monkeys ( Sapajus spp.) [Addessi et al, ; Visalberghi and Addessi, , ] and human children [Galloway et al, ] to overcome caution toward novel food.…”
Section: Discussionmentioning
confidence: 99%
“…Neophobia, in contrast, varies with stimulus complexity and the degree of deviation from what the organism has experienced before (variation) and the same may apply for exploration, innovation and learning . Several studies ranging from birds to mammals have shown that diet or habitat generalists are less neophobic than diet and habitat specialists supporting the Neophobia Threshold hypothesis stating that experiences made early in life (e.g. number of food types/habitats) are protected by neophobia later in life .…”
Section: Cognitive Adaptations To Stable Environmentsmentioning
confidence: 99%
“…In primates, most studies of novelty response conducted on captive groups describe neophilia [Addessi et al, 2007;Chamove, 1983;Ehrlich, 1970;Glickman & Sroges, 1966;Joubert & Vauclair, 1986;Visalberghi, 1988]. In contrast, the few available studies of wild primates report cautiousness toward novel artifacts [Menzel, 1966;Visalberghi et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Among non-primates, the only such comparison involves spotted hyenas, Crocuta crocuta, again with the same outcome [Benson-Amram et al, 2013]. Moreover, among primates, there is growing evidence for social influences on the integration of novel food items into feeding repertoires [Addessi et al, 2007;Leca et al, 2007;Schuppli et al, 2012;Ueno & Matsuzawa, 2005;Visalberghi & Addessi, 2000;Visalberghi & Fragaszy, 1995], suggesting that upon encounter with novelty, primates use social cues rather than risk-independent exploration.…”
Section: Introductionmentioning
confidence: 99%